1969
DOI: 10.1002/kin.550010606
|View full text |Cite
|
Sign up to set email alerts
|

Chemical kinetics of hydrogen halide lasers. 1. The H2Cl2 system

Abstract: A detailed kinetic model of the HCl chemical laser produced by the flash photolytically initiated H,-Cl, explosion is described, and the results of computer calculations on such a system are discussed. I t is shown that currently accepted values of the various rate constants, supplemented in a few cases by reasonable estimates of previously unmeasured rate constants, are adequate to approximate the observed laser behavior of this system. I t is also shown that the chemistry of such a system is extremely comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1971
1971
1982
1982

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…In a study, 4 7 of DF(v I -4) relaxation by D 2 , the rate coefficients were found to scale with v as V 0 .5 exp(-AE.,/RT), where AE,, is the energy mismatch of the exchange. *(The exothermic exchange in the reverse direction scales simply as v*) Using this analogy and the measured rate coefficient for exchange (13a), we obtain for exchange (15) the rate coefficients, k., No evidence of multiquantum proceses$ was found in the studies' 3 of UV(v -3,4) deactivation by HNV, D 2 , N2.…”
Section: Dself-relaxationmentioning
confidence: 92%
See 2 more Smart Citations
“…In a study, 4 7 of DF(v I -4) relaxation by D 2 , the rate coefficients were found to scale with v as V 0 .5 exp(-AE.,/RT), where AE,, is the energy mismatch of the exchange. *(The exothermic exchange in the reverse direction scales simply as v*) Using this analogy and the measured rate coefficient for exchange (13a), we obtain for exchange (15) the rate coefficients, k., No evidence of multiquantum proceses$ was found in the studies' 3 of UV(v -3,4) deactivation by HNV, D 2 , N2.…”
Section: Dself-relaxationmentioning
confidence: 92%
“…In our 1976 review we listed (Table 1) all the experimental data of which we were aware pertaining to the absolute measurement of k 3 ; relative measurements of k 3 were tabulated separately (Table 2), because at the time the absolute measurements were not of themselves sufficiently unambiguous to allow a precise determination of k 3 with great confidence.…”
Section: A F +mentioning
confidence: 99%
See 1 more Smart Citation
“…(4)(5)(6)(7)(8)(9) and by Eqs. (10)(11)(12)(13)(14)(15), respectively. In many cases of interest, the pumping reactions are diffusion-limited and occur in a thin zone, which can be approximated by a flame sheet.…”
Section: Methods Of Solutionmentioning
confidence: 98%
“…premixed, obviating the need to consider diffusion and convection effects altogether. 13 ) So that the presence of a nonequilibrium population distribution can be explicitly handled, the gas is treated as a mixture of several components, in much the same way as is done in the case of reacting gases, except that here each longlived vibrational level of the lasing molecule is treated as a separate component of the gas. Chemical formation of the lasing molecule by laminar mixing and combustion of fuel and oxidizer is assumed to be diffusion-controlled, i.e., combustion occurs along a flame sheet.…”
mentioning
confidence: 99%